2013
DOI: 10.1038/bjc.2013.290
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial expression of FHL2 is negatively associated with metastasis-free and overall survival in colorectal cancer

Abstract: Background:Four-and-a-half LIM domains protein 2 (FHL2) is a component of the focal adhesion structures and has been suggested to have a role in cancer progression. It has been shown to be overexpressed in the colorectal cancer (CRC).Methods:Here, we examined a possible prognostic value of FHL2 in CRC. Immunohistochemistry for FHL2 was performed on 296 CRCs without distant metastases at the time of surgery. Staining in the epithelial compartment was quantitatively evaluated using image analysis, and results we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…5F). Similar to many other cancers originating from prostate, ovary, gastrointestinal tract and the hematopoietic system [38][39][40], FHL2 is overexpressed in PDAC. While PDAC revealed a heterogeneous expression pattern throughout the whole specimen, FHL2 expression was predominant in the central area or invasion front in colorectal cancer in association with metachronous metastases [40] and determined overall survival independent from other clinicopathological variables.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…5F). Similar to many other cancers originating from prostate, ovary, gastrointestinal tract and the hematopoietic system [38][39][40], FHL2 is overexpressed in PDAC. While PDAC revealed a heterogeneous expression pattern throughout the whole specimen, FHL2 expression was predominant in the central area or invasion front in colorectal cancer in association with metachronous metastases [40] and determined overall survival independent from other clinicopathological variables.…”
Section: Discussionmentioning
confidence: 93%
“…Similar to many other cancers originating from prostate, ovary, gastrointestinal tract and the hematopoietic system [38][39][40], FHL2 is overexpressed in PDAC. While PDAC revealed a heterogeneous expression pattern throughout the whole specimen, FHL2 expression was predominant in the central area or invasion front in colorectal cancer in association with metachronous metastases [40] and determined overall survival independent from other clinicopathological variables. Moreover, FHL2 directly interacts with the epithelial-tomesenchymal marker Snail1 thereby negatively controlling E-cadherin transcriptional activity in colorectal cancer [41], a finding subsequently connected with TGF-β signaling and invasion [17].…”
Section: Discussionmentioning
confidence: 93%
“…Whole slide scanning and image analysis tools now enable to objectively and quantitatively evaluate IHC biomarkers in a whole tissue slide or a specific region of interest delineated by a pathologist. Compartmentalising the quantitative evaluation of IHC biomarkers in a specific histological structure, such as glandular epithelium in colorectal, breast or prostatic lesions, is often required in histopathology to provide more relevant and informative measurements for clinical research, as evidenced by Verset et al (2013Verset et al ( , 2015. For this purpose, pathologists have to annotate thousands of structures present in histological slide series, a long, tedious and potentially biased task that would greatly benefit from automation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a previous study reported that Rho signaling mediates nuclear localization of FHL2 in NIH 3T3 cells under serum-starved conditions (31). FHL2 is overexpressed in some highly metastatic cell lines and has dramatic effects on cell migration (32)(33)(34). Thus, FHL2 appears to have a number of signaling roles mediating communication between the cytoskeleton and the nucleus, but the molecular steps remain unclear.…”
mentioning
confidence: 99%